Analisis Kelayakan Finansial Dalam Peningkatan Kapasitas Kandang Di Usaha Peternakan Ayam Broiler Andien - Recha Anggardha; Widya Setiafindari (Jurnal Universal Technic, 2023)
The Broiler Chicken business owned by Andien, belonging to Mrs. Tri Winarti, initially operated with a capacity of 12,000 chickens and planned to expand to 24,000 chickens. This study aims to assess the sustainability of the development of Andien's Broiler Chicken farm to 24,000 chickens from a financial perspective. Financial analysis was conducted through calculations of Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), and Payback Period (PP). From the calculation results, it can be concluded that the expansion of Andien's Broiler Chicken business from 12,000 chickens to 24,000 chickens is a viable step based on the scenario calculations. The Payback Period (PP) is 1.31 periods, indicating a quick payback of investment as PP is less than 12 periods. The calculation results show an NPV value of Rp 4,936,714,867 using a 6% discount rate (based on the 2023 BRI KUR interest rate), and if using a 7% discount rate (based on the 2023 Mandiri KUR interest rate), the NPV would be 4,633,045,331. The presence of a positive NPV indicates the viability of this business development. The calculated IRR value reaches 22.26%, exceeding the 6% discount rate. The feasibility of the business is also supported by a BCR value of 1.09, where a ratio above 1 indicates the viability of the business.